ANALISIS PERBANDINGAN PENILAIAN KINERJA PERBANKAN MENURUT SE Bl 1997 DAN SE BI 1998 - Lydia Setyawardani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2004)
We can evaluate the bank health from financial  ratios in its financial  statements.  The fi nancial ratios are known as ('AMEL (capital adequacy, asset quality, management, earning, liquidity). The government changes the regulation of evaluation of bank health. The new regulation we use now is SE HI No. 30 23: UPPB, 19 March 1998 and the old one is SE Bl No. 30   2   UPPB. 30 April 1997.The research issue is whether /here any significant changes in bank performance if we use the new reKulation than the old one. The chanRes consist of three financial ratios there are two ratios <?f'asset quality and one liquidity ratio. The measurement calculates the credit values from .financial ratios according to the old regulation and the new one and then comparing the results.The results show that there are any signlficant changes in bank performance using the new regulation. The results also show that using the new regulation to measure the bank health makes more difficultj(Jr the bank to get the predicate as a good bank.